Comparison of finger flexion strength and muscular recovery of male lead sport climbers across climbing classes - Son, S.; Seo, Y.; Son, J.; Yun, S.; Lee, D. T. (Physical Therapy in Sport, 2024)
Background/objective The purpose of this study was to compare finger flexor strength (FS), finger flexor muscle recovery (FR), and forearm circumference (FC) across three different climbing classes in male lead sport climbers.